The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1103/physrevlett.49.501
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of Oxygen and Water on Ru (001): Vibrational and Structural Properties

Abstract: A thermally induced change in the vibrational properties of a coadsorbed oxygen-water overlayer on Ru(OOl) is attributed to the formation of a local 0-H 2 0 complex. An O-H stretching mode of this complex is observed in electron-energy-loss data, but not in infrared reflection-absorption data available from another laboratory. This provides the first direct experimental evidence of a case in which the surface dipolar selection rule applies in an infrared but not in an energy-loss measurement.PACS numbers: 82.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…After desorption, the exact same amount of O at is present at the surface as before water was adsorbed. In agreement with earlier studies, [2][3][4]12 we find that about five water molecules are affected per oxygen atom.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…After desorption, the exact same amount of O at is present at the surface as before water was adsorbed. In agreement with earlier studies, [2][3][4]12 we find that about five water molecules are affected per oxygen atom.…”
Section: Discussionsupporting
confidence: 94%
“…5,8 In view of the debate over partial dissociation of water on Ru͕0001͖, it is imperative to reevaluate the assumptions made by previous authors who generally assumed that water stays intact when interacting with oxygen. [2][3][4] Only in a recent infrared spectroscopy study by Clay et al 12 was the possibility of water dissociation pointed out when coadsorbed with low coverages of oxygen. Using temperature-programed desorption ͑TPD͒, Doering and Madey found a significant change in the overall shape of the desorption spectra between low and high oxygen coverages with a sharp transition between 0.20 and 0.25 ML O, indicating a change in the interaction of H 2 O and O adatoms on the surface.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dissociation is observed at low oxygen coverage ͑ Ͻ 0.2 ML͒ while it is inhibited at larger O coverage ͑ = 0.25-0.5 ML͒ contrary to studies that assume that water remains intact when interacting with oxygen. [6][7][8][9] Preadsorbed oxygen on the ruthenium surface does not only influence the dissociation characteristics of water but also its structure. On the p͑2 ϫ 2͒ oxygen terminated surface, water adsorbs in a p͑2 ϫ 2͒ symmetry, 4,10 compared to a hexagonal arrangement ͑ͱ3 ϫ ͱ 3͒R30°observed on clean hexagonalclose-packed metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Very extensive and revealing studies of water interaction with the Ru(0001) surface were performed by Thiel et al [130,131] using a variety of techniques (TDS, AES, HREELS, UPS, and ESDIAD = electron-stimulated desorption ion angular distribution). The authors observed several binding states in their TD spectra which develop simultaneously with H 2 O exposure, again indicating that a first and a second water layer grow at the same time, whereby the second layer is H-bonded to the first layer.…”
Section: Water On Metal Surfacesmentioning
confidence: 99%